The Task Pre-Configuration Is Associated With Cognitive Performance Evidence From the Brain Synchrony - Xiang, Jie; Fan, Chanjuan; Wei, Jing; Li, Ying; Wang, Bin; Niu, Yan; Yang, Lan; Lv, Jiaqi; Cui, Xiaohong (Frontiers in Computational Neuroscience, 2022)
Although many resting state and task state characteristics have been studied, it is still unclear how the brain network switches from the resting state during tasks. The current theory shows that the brain is a complex dynamic system and synchrony is defined to measure brain activity. The study compared the changes of synchrony between the resting state and different task states in healthy young participants (N = 954). It also examined the ability to switch from the resting state to the task-general architecture of synchrony. We found that the synchrony increased significantly during the tasks. And the results showed that the brain has a task-general architecture of synchrony during different tasks. The main feature of task-based reasoning is that the increase in synchrony of higher-order cognitive networks is significant, while the increase in synchrony of sensorimotor networks is relatively low. In addition, the high synchrony of high-order cognitive networks in the resting state can promote task switching effectively and the pre-configured participants have better cognitive performance, which shows that spontaneous brain activity and cognitive ability are closely related. These results revealed changes in the brain network configuration for switching between the resting state and task state, highlighting the consistent changes in the brain network between different tasks. And there was an important relationship between switching ability and cognitive performance.